2019
DOI: 10.2139/ssrn.3317570
|View full text |Cite
|
Sign up to set email alerts
|

Hedging Climate Change News

Abstract: We propose and implement a procedure to dynamically hedge climate change risk. We extract innovations from climate news series that we construct through textual analysis of newspapers. We then use a mimicking portfolio approach to build climate change hedge portfolios. We discipline the exercise by using third-party ESG scores of firms to model their climate risk exposures. We show that this approach yields parsimonious and industry-balanced portfolios that perform well in hedging innovations in climate news b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…While Baker, Hollifield, and Osambela (2018) and Roth Tran (2019) present theoretical models in which green or emission-oriented investors can hedge risks by investing in polluters, Andersson, Bolton, and Samama (2016) show empirically that investors can hedge against potential future prices on carbon emissions by investing in a decarbonized index. Engle, Giglio, Kelly, Lee, and Stroebel (2018) develop a climate change news index and assess strategies that can hedge an investor against such news. In contrast to these papers, we focus on market dynamics that reflect investor behavior around specific disaster events that occur at a local level.…”
Section: Related Literaturementioning
confidence: 99%
“…While Baker, Hollifield, and Osambela (2018) and Roth Tran (2019) present theoretical models in which green or emission-oriented investors can hedge risks by investing in polluters, Andersson, Bolton, and Samama (2016) show empirically that investors can hedge against potential future prices on carbon emissions by investing in a decarbonized index. Engle, Giglio, Kelly, Lee, and Stroebel (2018) develop a climate change news index and assess strategies that can hedge an investor against such news. In contrast to these papers, we focus on market dynamics that reflect investor behavior around specific disaster events that occur at a local level.…”
Section: Related Literaturementioning
confidence: 99%
“…Proponents like Carney who support the climate-financial fragility view proffer that adverse climate poses fragility to the financial system given the damaging impact on the physical property (Carney, 2015;Giglio & Xu, 2019;Giglio, Maggiori, Stroebel, Weber, 2019). Thus, climate change policies carry inherent financial risks through disruptions to business models (Engle et al, 2020), and may exacerbate the credit risk of financial transactions, impair financial markets, and pose long-term damaging effects A. Climate Risk Damages Property, Plant and Equipment (PPE)…”
Section: Climate Change Is a Source Of Financial Riskmentioning
confidence: 99%
“…It can also result in stranded assets that are no longer productive in the real economy. Engle, Giglio, Kelly, Lee & Stroebel (2020) implement a procedure to dynamically hedge climate risk through textual analysis of newspapers to extract innovations from climate news series. Engle et al (2020) utilized insights from portfolio theory, options and asset pricing to build climate change hedge portfolios and showed that their method yields industry-balanced portfolios that perform well in hedging innovations in climate news both in-sample and out-of-sample.…”
Section: Climate Financial Risk Can Be Transmitted Through Systemimentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to the dynamic evolution of the network over time, we find that some sectors become more or less 1 All codes have been written in R and are available for download at http://www.gustavo-schwenkler.com. 2 NLP has become increasingly popular in economics research; see Engle et al (2019) and Jelveh et al (2018) for recent applications of NLP for the analysis of climate change and the influence of political partisanship. 3 We show in an online appendix that the majority of the economically relevant information about firm links is communicated in individual sentences rather than across sentences of a news article, validating our approach.…”
Section: Introductionmentioning
confidence: 99%